Evaluation of prognostic factors affecting root coverage in patients before planned orthodontic treatment - Górski, Bartłomiej; Górska, Renata (Forum Ortodontyczne / Orthodontic Forum, 2018)
During orthodontic dental arch expansion, especially in cases of teeth with gingival recessions, further loss of soft tissues and progression of recession might be observed. Aim. The aim of this study was to evaluate determinants of root coverage, increase in the width of keratinised tissue and gingival thickness after soft tissue augmentation procedures in patients before planned orthodontic treatment. Material and methods. 16 patients with the mean age of 28.18 (±6.58) years with 122 type I and II gingival recessions were enrolled in the study. Total, 32 soft tissue augmentation procedures with a coronally advanced flap (CAF) and tunnel technique (TUN) together with a connective tissue graft (CTG) were performed. The clinical and aesthetic parameters were assessed at baseline and 6 months postoperatively. Results. CAF was performed more often in upper teeth and type I gingival recession, in contrast to TUN. The mean percentage root coverage on CAF sides was 98.48%, while on TUN sides it was 81.71%. Complete root coverage was achieved in 87.3% and 61.2% of gingival recessions, respectively. A multivariate linear regression showed that the amount of root coverage was significantly affected by baseline recession height (GR), recession type, type and position of a tooth and surgical modality. The increase in the width of keratinised tissue (WKT) was related to the baseline width of keratinised tissue, type and position of a tooth, whereas the increase in gingival thickness (GT) was associated with baseline gingival thickness, tooth position and gender. Best aesthetics was observed on the TUN sides. Conclusions. Baseline characteristics of a surgical site (GR, WKT, GT), recession type, position and type of a tooth, and treatment modality may be helpful in the prognosis of recession coverage, increase in the width of keratinised tissue and gingival thickness in orthodontic patients. (Górski B, Górska R. Evaluation of prognostic factors affecting root coverage in patients before planned orthodontic treatment. Orthod Forum 2018; 14: 257-69).